Sentinel node identification technique in melanoma localized on the skin of the upper part of the back - Jastrzębski, Tomasz; Lass, Piotr; Drucis, Kamil (Contemporary Oncology/Współczesna Onkologia, 2009)
Sentinel lymph node mapping in patients with extremity or trunk melanoma is a simple procedure with a high identification rate. Mapping in patients with dorsal melanoma is a technically demanding procedure due to scattered radiation of the peritumoural injection site screening off the radiation of the isotope in the lymph nodes. The article presents technique that facilitates axillary sentinel lymph node mapping in those patients. The patient is placed in a prone position and the injection site is covered with lead plate. This procedure diminishes scattered radiation of the injection site and enables intraoperative identification. Positive preoperative lymphatic mapping confirms nodal uptake of the isotope and simplifies intraoperative identification with a handheld gamma probe